Corruption in Public Discourses: A Comparison Between Colombian and European Metaphors. (4th July 2021) - Isaza, Carolina; Ossewaarde, Ringo
Abstract : This article addresses the metaphors about corruption from a comparison between public discourses in European and in Colombian media. Using Conceptual Metaphor Theory and content analysis, we pose three research questions: What are the metaphors associated with political or public corruption in Colombia and Europe? Are they similar or different? What implications do these metaphors have for public discourse, thought, and action related to corruption issues? We identify new source domains for metaphors on corruption, and structure them in a logical framework. The results show surprising similarities between discourses in the two contexts. We conclude with an analysis of the implications that these metaphorical constructions have for decision and policy making regarding corruption in public administration.